Whole-Body Electromyostimulation Improves Performance-Related Parameters in Runners - Amaro-Gahete, Francisco J.; De-la-O, Alejandro; Sanchez-Delgado, Guillermo; Robles-Gonzalez, Lidia; Jurado-Fasoli, Lucas; Ruiz, Jonatan R.; Gutierrez, Angel (Frontiers in Physiology, 2018)
The aim of this study was to study the effects of a 6-session (one per week) WB-EMS training intervention on maximum oxygen uptake, aerobic and gas exchange thresholds, running economy, and muscular power in male recreational runners. Twelve men were randomized into WB-EMS intervention (n=6; 27.0 ± 7.5 years; 70.1 ± 11.1 kg; 1.75± 0.5 m) or control (n=6; 27.0 ± 6.1 years; 73.6 ± 3.4 kg; 1.77± 0.3). The WB-EMS group reduced the running training frequency to one per week and followed one WB-EMS training session per week during 6 weeks. Participants in the control group maintained their usual running endurance training. Each participant completed four assessments: physiological parameters [(i) VO2max, aerobic and gas exchange threshold values, and (ii) running economy at two intensities], muscular power (vertical jump), and anthropometric parameters both at baseline and after the intervention. Participants in the WB-EMS group improved VO2max, aerobic and gas exchange threshold values, running economy, and vertical jump (p<0.05) compared to the control group. There, WB-EMS seems to be an effective training methodology leading to improvements in performance during endurance training volume reduction in male recreational runners.